Wildlife in urban parks—why sustain it? - Luniak, Maciej (Polskie Studia Krajobrazowe, 2019)
The author argues that it is not possible, especially in an urbanized landscape, to trace any clear dividing lines between natural structures and processes and those caused by the human. Simplifying things to the extreme, we assume that “wildlife” includes those organisms which live permanently (or are capable of living) in a given area without any deliberate human assistance. Arguments for sustaining “wild life” in city parks are many, deriving from humanitarian, ecological, social, or economic considerations. The author acquaints the reader with research conducted as part of the project Nature of the Skaryszewski Park. The diagnosis relating to that Warsaw park enabled the formulation of a range of recommendations whose application would protect and foster living nature in city parks.